Dual-use nano-neurotechnology: An assessment of the implications of trends in science and technology. (29th November 2018) - Nixdorff, Kathryn; Borisova, Tatiana; Komisarenko, Serhiy; Dando, Malcolm
Abstract : The chemical and biological nonproliferation regime stands at a watershed moment, when failure seems a real possibility. After the unsuccessful outcome of the 2016 Eighth Review Conference, the future of the Biological and Toxin Weapons Convention is uncertain. As the Chemical Weapons Convention (CWC) approaches its Fourth Review Conference in 2018, it has almost completed removing the huge stocks of chemical weapons, but it now faces the difficult organizational task of moving its focus to preventing the reemergence of chemical weapons at a time when the international security situation appears to be increasingly more difficult and dangerous. In this article, we assess the current and near-term state (5–10 years) and impact of three related areas of science and technology that could be of dual-use concern: targeted delivery of agents to the central nervous system (CNS), particularly by means of nanotechnology; direct impact of nanomaterials on synaptic functions in the CNS; and neuronal circuits in the brain that might be targeted by those with hostile intent. We attempt to assess the implications of our findings, particularly for the consideration of the problem of state-level interest in so-called nonlethal incapacitating chemical agents for law enforcement at the CWC Review Conference in 2018, but also more generally for the longer-term future of the chemical and biological nonproliferation regime.